Analisis Vertikal dan Horizontal Dalam Pencapaian Pendapatan dan Pertumbuhan laba PT. Garuda Indonesia, Tbk Pada Masa Pandemi - Maulana, Wahyu; Rahayu, Runik Puji (Universitas Gajah Putih, 2022)
Conditions during the pandemic made all companies experience unfavorable conditions in obtaining income and achieving profits so that it affected financial performance. PT. Garuda Indonesia, Tbk. This study aims to measure the company's financial performance using vertical and horizontal analysis with financial reports published in the period 2018 to 2020 as the main data. The results show that the vertical analysis of financial performance is not optimal because the number of short-term debt and operating expenses increases so that it affects profit, horizontally shows a negative trend in the percentage of the company's operating profit, especially in 2019 to 2020.